Makna Kekudusan Menurut 1 Petrus 1:13-25 - Lorensia Fransiska; Yusak Sigit Prabowo (Sekolah Tinggi Teologi Torsina, 2021)
Holiness is often discussed in the Christian life and becomes an inseparable part of the believer. This paper tries to review holiness based on the letter 1 Peter 1:13-25. With a hermeneutical approach, the biblical text describes the understanding of holiness according to 1 Peter 1:13-25. From the results of this study, it is concluded that holiness means separation, can take place in the minds of believers, must be both